Hexavalent Chromium Removal from Model Water and Car Shock Absorber Factory Effluent by Nanofiltration and Reverse Osmosis Membrane - Amine Mnif; Imen Bejaoui; Meral Mouelhi; Béchir Hamrouni (International Journal of Analytical Chemistry)
Nanofiltration and reverse osmosis are investigated as a possible alternative to the conventional methods of Cr(VI) removal from model water and industrial effluent. The influences of feed concentration, water recovery, pH, and the coexisting anions were studied. The results have shown that retention rates of hexavalent chromium can reach 99.7% using nanofiltration membrane (NF-HL) and vary from 85 to 99.9% using reverse osmosis membrane (RO-SG) depending upon the composition of the solution and operating conditions. This work was also extended to investigate the separation of Cr(VI) from car shock absorber factory effluent. The use of these membranes is very promising for Cr(VI) water treatment and desalting industry effluent. Spiegler-Kedem model was applied to experimental results in the aim to determine phenomenological parameters, the reflection coefficient of the membrane (σ), and the solute permeability coefficient (Ps). The convective and diffusive parts of the mass transfer were quantified with predominance of the diffusive contribution.